(untitled) (Delta Medical College Journal, 2024)
Background: Online learning is the major concept in education which converts the traditional educational shape into a new form that transforms in person or physical learning into a virtual approach of learning. It is an alternative to traditional classroom learning and involves using primarily the internet and one or more other technologies. Objective: This study explores the perception of students regarding its benefits and challenges and recommendations. Materials and method: Data were collected from 273 students of 1st and 2nd year MBBS from January 2021 to February 2021 at Enam Medical College, Savar, Dhaka, Bangladesh, using a predesigned validated questionnaire. Results: The findings of the present study revealed that most of the students lack in academic or institutional knowledge regarding the ICT tools used in online learning process. The benefits included its flexibility regarding the time and place, sharing of information is easy and cost effective and allows mass audiences. Whereas, less effective in practice-based learning, instant feedback is difficult, lack of attentiveness, disturbance of physical health and diminished social interaction were identified as major disadvantages Conclusion: Online learning has its own set of advantages and disadvantages as other teaching methods. The purpose of this study was to assess the current state of online learning activities from the students’ perspective. Delta Med Col J. Jan 2021;9(2): 69-74